2013
DOI: 10.1038/jp.2013.63
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal heart rate characteristics before clinical diagnosis of necrotizing enterocolitis

Abstract: ObjectiveEarlier diagnosis and treatment of necrotizing enterocolitis (NEC) in preterm infants, prior to clinical deterioration, might improve outcomes. A monitor that measures abnormal heart rate characteristics (HRC) of decreased variability and repetitive decelerations was developed as an early warning system for sepsis. Since NEC shares pathophysiologic features with sepsis, we tested the hypothesis that abnormal HRC occur prior to clinical diagnosis of NEC.Study DesignRetrospective review of Bells stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 33 publications
0
69
1
Order By: Relevance
“…FHR and fHRV are regulated by a complex interplay of the parasympathetic and sympathetic nervous systems accounting for the baseline FHR as well as short-term and long-term fHRV showing linear and nonlinear properties (Frasch et al 2009). These fHRV properties are differentially affected by LPS-induced fetal and neonatal inflammatory response (Lake et al 2002, Stone et al 2013. Decreased fetal and neonatal HRV and transient repetitive heart rate decelerations coincide with or precede clinical signs of sepsis (Rudolph et al 1965, Cabal et al 1980, Fairchild and O'Shea 2010.…”
Section: Discussionmentioning
confidence: 99%
“…FHR and fHRV are regulated by a complex interplay of the parasympathetic and sympathetic nervous systems accounting for the baseline FHR as well as short-term and long-term fHRV showing linear and nonlinear properties (Frasch et al 2009). These fHRV properties are differentially affected by LPS-induced fetal and neonatal inflammatory response (Lake et al 2002, Stone et al 2013. Decreased fetal and neonatal HRV and transient repetitive heart rate decelerations coincide with or precede clinical signs of sepsis (Rudolph et al 1965, Cabal et al 1980, Fairchild and O'Shea 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Some neonatal units are now incorporating sophisticated analysis algorithms into their bedside monitoring, and ultimately these may provide just such a prediction tool. Abnormal heart rate characteristics have been suggested as a useful clinical tool to predict sepsis [25], and have shown initial promise to predict NEC before clinical diagnosis in a prospective trial setting [26]. However, a more recent study in which the same system was used in routine clinical practice suggested that abnormal heart rate characteristics have limited ability to detect sepsis [27].…”
Section: Improved Diagnostic Methodsmentioning
confidence: 99%
“…Neonates may experience abdominal distention with or without overlying skin changes, feeding intolerance/emesis, decreased or absent bowel sounds, increased pre-feeding gastric residuals, and blood in the stool. Other more systemic symptoms include hypotension, poor perfusion, increased bradycardic or apneic events, worsening respiratory status, glucose instability, abnormal heart rate, and temperature instability (1,2,14).…”
Section: Clinical Presentationmentioning
confidence: 99%